Mechanism, Prevention, and Treatment of Radiation-Induced Salivary Gland Injury Related to Oxidative Stress - Zijing Liu (MDPI AG, 2021)
Radiation therapy is a common treatment for head and neck cancers. However, because of the presence of nerve structures (brain stem, spinal cord, and brachial plexus), salivary glands (SGs), mucous membranes, and swallowing muscles in the head and neck regions, radiotherapy inevitably causes damage to these normal tissues. Among them, SG injury is a serious adverse event, and its clinical manifestations include changes in taste, difficulty chewing and swallowing, oral infections, and dental caries. These clinical symptoms seriously reduce a patient’s quality of life. Therefore, it is important to clarify the mechanism of SG injury caused by radiotherapy. Although the mechanism of radiation-induced SG injury has not yet been determined, recent studies have shown that the mechanisms of calcium signaling, microvascular injury, cellular senescence, and apoptosis are closely related to oxidative stress. In this article, we review the mechanism by which radiotherapy causes oxidative stress and damages the SGs. In addition, we discuss effective methods to prevent and treat radiation-induced SG damage.